Morbidity Pattern Among Primary Schoolchildren in A Rural Area Of Uttar Pradesh - Rani, Vidya; Srivastava, Dhiraj Kumar; Jain, Pankaj Kumar; Kumar, Sandeep; Singh, Naresh Pal; Dixit, Anand Mohan (National Journal of Community Medicine, 2014)
Background: Health of the child is viewed as absence of disease not as comprehensive health in the developing Countries. The present study was conducted with the objectives to assess the morbidity pattern among school children in rural area of Mainpuri and to find out the status of personal hygiene among primary school children. Methods: The present study was a field based cross-sectional study carried out for a period of 3 months from December 2013 to February 2014 in a randomly selected primary school of block karhal in rural area of district Manipuri, Uttar Pradesh. A list of all the students was obtained and days were fixed for examination of the students after consultation from the principal. For data collection we used predesigned, pretested structured questionnaire. . Result: A total of 171 children were examined, amongst them 71 (42.71 %) children were having more than one ailment at the time of examination. Main problems observed were dental problems (35.78%), wax in the ear (33.91%), nutritional anemia (26.90%) and poor personal hygiene (34.5%) among children. Conclusion: Dental problems, nutritional anaemia and poor personal hygiene were more common among school children. Therefore, there is need for parents and teachers as agent of health promotion to enshrine the value of personal hygiene in school children.